Evolution of Denmark Strait overflow cyclones and their relationship to overflow surges - Almansi, Mattia; Haine, Thomas W. N.; Gelderloos, Renske; Pickart, Robert S. (Geophysical Research Letters, 2020)
© The Author(s), 2020. This article is distributed under the terms of the Creative Commons Attribution License. The definitive version was published in Almansi, M., Haine, T. W. N., Gelderloos, R., & Pickart, R. S. Evolution of Denmark Strait overflow cyclones and their relationship to overflow surges. Geophysical Research Letters, 47(4), (2020): e2019GL086759, doi:10.1029/2019GL086759. Mesoscale features present at the Denmark Strait sill regularly enhance the volume transport of the Denmark Strait overflow (DSO). They are important for the Atlantic Meridional Overturning Circulation and ultimately, for the global climate system. Using a realistic numerical model, we find new evidence of the causal relationship between overflow surges (i.e., mesoscale features associated with high‐transport events) and DSO cyclones observed downstream. Most of the cyclones form at the Denmark Strait sill during overflow surges and, because of potential vorticity conservation and stretching of the water column, grow as they move equatorward. A fraction of the cyclones form downstream of the sill, when anticyclonic vortices formed during high‐transport events start collapsing. Regardless of their formation mechanism, DSO cyclones weaken starting roughly 150 km downstream of the sill, and potential vorticity is only materially conserved during the growth phase. This material is based upon work supported by the National Science Foundation under Grants OCE‐1433448, OCE‐1633124, OCE‐1756361, and OCE‐1756863. The numerical model was run on the Maryland Advanced Research Computing Center (MARCC). Marcello Magaldi helped to configure the model. OceanSpy and several packages from the Pangeo software ecosystem have been used to postprocess the model output. The numerical solutions are publicly available on SciServer (http://sciserver.org), which is developed and administered by the Institute for Data Intensive Engineering and Science at Johns Hopkins University. Instructions for accessing the data set are available at this site ...